Assessing Adoption of Gross Margin Analysis Technique by Farmer Business School Lead Farmers in Mzuzu and Karonga Agriculture Development Divisions of Malawi - Beatrice Mbakaya; D. Kambewa; Isaac Mambo (Journal of Agricultural Extension Management, 2017)
Gross margin analysis technique is among the tools that farmers are taught in farmer business schools to enable them to plan/or profitable enterprises. This study was aimed at assessing the adoption of this technique being promoted among lead farmers. It was observed that 60 per cent of the respondents did not prepare gross margins, indicating low adoption of this technique. Among the users of gross margin technique, this was used in selection of profitable enterprises only. Most of the respondents (60%) had an average knowledge on gross margin technique. Most respondents (82%) however indicated that it is easy to do gross margin analysis. Moreover, farmers complained that they do not sell their products at calculated sale prices. Use of gross margin technique was found to be associated with availability of farm records, extension follow up visits on gross margin analysis and farmers’ knowledge on gross margin analysis